Construction and validation of an online training programme to promote resilience and mindfulness, including empathy, compassion, and gratitude - Bock, Lotte (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2025)
This cumulative dissertation presents the construction and validation of three structured online training programmes aimed at promoting resilience and mindfulness, with a consistent integration of empathy, compassion, and gratitude across all interventions. Each programme—focusing respectively on Compassion and Gratitude, Mindfulness, and Resilience—was conceptualised, developed, and delivered by the author within a standardised 28-day framework requiring 15–20 minutes of daily practice. To assess external validity and applicability across diverse populations, the interventions were evaluated in distinct target groups: women under 40 with low self-empathy, individuals with multiple sclerosis, care staff, and distance-learning students. Across studies, the programmes demonstrated promising effects in enhancing psychological well-being and cultivating adaptive socio-emotional skills. Together, the findings provide evidence for the effectiveness and scalability of brief, digitally delivered training formats to strengthen resilience- and mindfulness-related outcomes in varied real-world contexts.
Keywords: Training; Internet-based; Resilience; Mindfulness; Compassion; Empathy; Gratitude; 150 Psychologie